2017
DOI: 10.1177/1076029617700997
|View full text |Cite
|
Sign up to set email alerts
|

Residual Vein Thrombosis Echogenicity Is Associated to the Risk of DVT Recurrence: A Cohort Study

Abstract: Although deep vein thrombosis (DVT) recurrence is a common late complication of the disease, there are few predictive markers to risk-stratify patients long-term after the thrombotic event. The accuracy of residual vein thrombosis (RVT) in this context is controversial, possibly due to a lack of a standardized methodology. The objective of the study was to evaluate the accuracy of RVT echogenicity as a predictive marker of late DVT recurrence. To evaluate the accuracy of RVT echogenicity as a predictive marker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…The presence of residual vein thrombosis was a condition reported in about 20% of patients referred for extended AT; this was in line with many scientific data pointing to a relationship between the persistence of a residual thrombus and an increased risk of thrombosis recurrence. 21 23 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of residual vein thrombosis was a condition reported in about 20% of patients referred for extended AT; this was in line with many scientific data pointing to a relationship between the persistence of a residual thrombus and an increased risk of thrombosis recurrence. 21 23 …”
Section: Discussionmentioning
confidence: 99%
“…The presence of residual vein thrombosis was a condition reported in about 20% of patients referred for extended AT; this was in line with many scientific data pointing to a relationship between the persistence of a residual thrombus and an increased risk of thrombosis recurrence. [21][22][23] On the basis of positive results of clinical trials, 24,25 the attending physicians suggested to about one-fourth of the patients who discontinued AT to assume sulodexide or aspirin as a substitute treatment in the months that followed. In some patients, the therapy for extended treatment was shifted from full-to low-dose apixaban; this was supported by results obtained in the Amplify-Extension trial 26 in which low-dose apixaban (2.5 mg twice daily) proved equally effective as and safer than standard dose (5 mg twice daily) for extended treatment, while in all the remaining cases the original AT was maintained also for extended therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The blood flow in the distal inflow tract is closely correlated to the patency rate of deep veins. 18 For patients with May-Thurner syndrome complicated with acute LEDVT, although both AngioJet and CDT can remove the thrombus, the anatomical abnormalities cannot be changed, and when only thrombectomy is performed without correcting the lesions of the iliac vein itself, this would likely cause thrombosis recurrence. Hence, the active and effective treatment of iliac vein stenosis is an important link to ensure efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…[46][47][48][49] Residual venous obstruction in patients with treated unprovoked DVT was an overall weak predictor for recurrence according to metaanalysis data, 47,50 while results from studies in specific subsets of patients have shown an increased risk of recurrence. 40,[51][52][53] In addition to the varying use of reference examinations in clinical practice, there is no consensus for the use of residual vein obstruction measurements in predicting recurrence or a standardized methodology for the measurements. 19,22,54 In current guidelines, venography and computed tomography (CT) venography are only suggested if CUS is unavailable or results are inadequate.…”
Section: Imaging Techniquesmentioning
confidence: 99%